The aggravation of arthritis by periodontitis is dependent of IL-17 receptor A activation - de Aquino, Sabrina G. [UNESP]; Talbot, Jhimmy; Sônego, Fabiane; Turato, Walter M.; Grespan, Renata; Avila-Campos, Mario J.; Cunha, Fernando Q.; Cirelli, Joni A. [UNESP] (Wiley, 2017)
Aim: To evaluate whether Porphyromonas gingivalis-induced periodontitis aggravates the antigen-induced arthritis (AIA) model, and whether this effect is dependent on the Th17/IL-17 signalling pathway. Materials and methods: Antigen-induced arthritis was triggered by local injection of methylated bovine serum albumin into the knee joint of previously immunized C57BL/6 wild-type (WT) and IL-17 receptor A (IL-17RA)-knockout mice. Periodontal disease in naïve or arthritic mice was induced by oral infection with P. gingivalis. Animals were sacrificed 7, 15 and 30 days after infection. Alveolar bone loss, joint histopathology, articular hyperalgesia and joint cytokine production were assessed, in addition to the proportion of Th17 and Treg cells isolated from the inguinal lymph nodes. Results: No influence of experimentally-induced arthritis was found on the alveolar bone resorption induced by P. gingivalis. However, mice with experimentally-induced arthritis that were exposed to P. gingivalis presented higher joint damage and Th17 frequencies when compared to non-infected mice. The aggravation of arthritis by periodontitis was accompanied by increased TNF and IL-17 production and articular neutrophil infiltration, whereas arthritis aggravation and changes in neutrophil infiltration were absent in IL-17RA-deficient mice. Conclusion: The effects of P. gingivalis-induced periodontitis on arthritis are dependent on Th17 expansion and IL-17RA signalling, which lead to increased neutrophil infiltration into the joints.
Keywords: antigen-induced arthritis; IL-17; oral microbiota; periodontal disease; Porphyromonas gingivalis; rheumatoid arthritis